(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The application of psychological theories to improve the outcomes of education has recently gained a lot of attention. An example of this is the Myers Briggs Type Indicator (MBTI) which is a personality test rooted in Carl Jung’s psyccentury, MBTI places people into 16 distinct categories, each containing a specific and unique combination of preferences and associated traits. Although MBTI has been popular in career advices and corporate environments, its possible importance in the education framework is mostly overlooked. This thesis illustrates the potential of MBTI in giving clear frameworks to students’ learning styles, their emotional and mental developmental phases as well as the interactions they have with the teachers. With the knowledge of different personality types, teachers would have the opportunity to adjust their lessons, as well as career guidance processes, and manage behavioral misconceptions in the classroom. This research aims to propose the idea that if applied sensibly, MBTI could be remarkably effective in fostering a student’s academic and personal development.